The analysis of sizes of physical loads at the period of special training in goalball - Bolach Eugeniusz; Bolach Bartosz; Migasiewicz Juliusz; Paliga Zdzislaw; Prystupa Tetyana; Marciniszyn Elzbieta (Kharkov National Pedagogical University, 2012)
The aim of study is to analyze the size of the physical loads used in practice in the subperiod microcycles of special preparation of visually impaired goalbal athletes. The study was performed at the beginning of the introductory microcycle and at the end of the subperiod shock microcycle of special preparation. This analysis concerned the comparison of mean values of heart rate obtained by the players in the test and training units of the slope (gradient) of the curve of the changes in heart rate in each of the separate parts of training. The study was conducted using the Polar S-810i sporttester. For more thorough analysis of the size of the physical load readings were used the following average values of heart rate players: rest, after warming up, the main part and after 15 minutes of restitution, made in two microcycles in the preparation of a special sub-period. The research concerned of 6 person goalball team "Start" in Wroclaw (training three times a week). The team included the visually impaired to various ocular defects, starting in the class B2. The obtained results allowed to determine the physical size of the applied load at the visually impaired athletes in goalball and the influence of these charges on improving their physical fitness and adaptation to training loads applied. The structure of training loads in two microcycles trainings, preparation of a special sub-period of visually impaired athletes in goalball had a significant impact on the adaptive changes in the behavior of heart rate (HR) and development of forms of sports players.